M2 microglia/macrophages drive oligodendrocyte differentiation during CNS remyelination - Miron, Veronique E. (2013)
The lack of therapies for progressive multiple sclerosis highlights the need to understand the regenerative process of remyelination that can follow CNS demyelination. This involves an innate immune response consisting of microglia/macrophages, which can be polarized to distinct functional phenotypes: proinflammatory (M1) or anti-inflammatory/immunoregulatory (M2). Here we show that a switch from an M1- to M2-dominant response occurred within microglia and peripherally-derived macrophages as remyelination started. Oligodendrocyte differentiation was enhanced in vitro with M2 conditioned media, and impaired in vivo following intra-lesional M2 depletion. M2 densities were increased in lesions of aged mice in which remyelination was enhanced by parabiotic coupling to a younger animal, and in MS lesions that normally show remyelination. Blocking M2-derived activin-A inhibited oligodendrocyte differentiation during remyelination in cerebellar slice cultures. Our results therefore show that M2 polarization is essential for efficient remyelination and identify activin-A as a novel therapeutic target for CNS regeneration.